ГЕНДЕРНЫЙ ПОДХОД К АНАЛИЗУ ЖЕНСКОЙ ДВОЙСТВЕННОСТИ: МИФОЛОГИЯ И РЕАЛЬНОСТИ - РАК, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
В статье рассматривается специфика женской двойственности в христианской традиции восточных славян при помощи гендерного подхода. Особенное внимание уделяется влиянию христианских образов (Евы и Марии) на реальное положение женщины. Миф и реальность оказываются тесно взаимосвязаны в контексте проблематики. Рак В.А. ГЕНДЕРНИЙ ПІДХІД ДО АНАЛІЗУ ЖІНОЧОЇ ДВОЇСТОСТІ: МІФОЛОГІЯ І РЕАЛЬНОСТІ У статті розглядається специфіка жіночої двоїстості в християнській традиції східних слов’ян за допомогою гендерного підходу. Особлива увага приділяється впливу християнських образів (Єви і Марії) на реальне положення жінки. Міф і реальність виявляються тісно взаємозв’язані в контексті проблематики. Ключові слова: Гендер, двоїстість, образ, «жіноча історія», стереотипність. Rak V.A. GENDER APPROACH TO THE FEMALE DUALITY ANALYSIS: MYTHOLOGY AND REALITY In the article the specific of woman duality is examined in christian tradition of east slavs through gender approach. The special attention is spared to influence of christian characters (Eva and Maria) on the real position of woman. A myth and reality appear closely associate in the context of range of problems. Keywords: Gender, duality, character, «woman history», stereotype.